Teacher Education in Higher Education Systems during Pandemic and the Synergy of Digital Technology - Vlasova, Elena Z. (2020)
In the modern world of education, the level of digital technology development plays a decisive role in the competitiveness of educational institutions. The transition to digital education is considered a key driving force for the development of any university. In recent years, pedagogical universities have made tangible progress in many areas of digital development. However, the introduction of digital technologies (DT) in the educational process reached its peak during the pandemic. This study aims to identify the distinctive features in the work of a teacher at a pedagogical university during the pandemic. The study revealed the following: the doubts of the teachers with no e-learning experience; didactically effective digital technologies in the educational process, the combined use of which ensures the synergistic effectiveness of e-learning; students’ attitude towards the quality of the e-learning process during the pandemic. Given the identified problems and positive aspects, the results of the study can be used to further develop a strategy for the digitalization of teacher education. The study proved that effective digitalization of the educational process is possible under the condition of cooperative and systematic work of all participants.